MENINGKATKAN KEMAMPUAN BERBAHASA ANAK USIA 5-6 TAHUN MELALUI KEGIATAN BERMAIN PERAN DI TK NEGERI 7 LEKO DESA BONTOMARANNU KECAMATAN MONCONGLOE KABUPATEN MAROS - Andi Besse Marda (ALGAZALI INTERNATIONAL JOURNAL EDUCATIONAL RESEARCH, 2018)
The purpose of this study was to improve language skills in children aged 5-6 years through media role playing in kindergarten. Country 7 Leko Bontomarannu Village Moncongloe District Maros Regency. The approach used in this study is a Qualitative approach with this type of research is Classroom Action Research (CAR) in its implementation consists of 2 (two) cycles, where each cycle consists of 3 meetings. Research focus on children's language skills. Data collection techniques in research are observation and documentation. The subjects of this study were group B children aged 5-6 years. The results showed that children's language skills in the 5-6 year age group in Kindergarten Negeri 7 Leko in Bontomarannu Village, Moncongloe District, Maros Regency had improved quite well. Improvement achieved by children in language skills where children have been able to retell activities that have been carried out simply. Children are able to mention the types of goods traded in the buying and selling process, children are able to offer goods that are traded, children are able to mention the price of goods sold, receive money and return it appropriately.Keywords: Ability to Speak and Play Role